Teletandem and telepresence: Rethinking the cultural component in language teaching and language teacher education - Salomão, Ana Cristina Biondo [UNESP] (My University, 2015)
This articles discusses some of the results of a qualitative ethnographic research on foreign language teacher's conceptions of culture in an extension course for continuing education in the virtual collaborative learning context of Teletandem Brazil: foreign languages for all, UNESP. The results have implications for the fi elds of language teaching and learning mediated by new technologies and teacher education. They suggest that telepresence in teletandem provided a means for dialogically undergoing the complexities of cultural experiences. Grounded in real world interaction, these experiences can lead to the change of the knowledge base of language teacher education for intercultural communication and the teaching and learning of culture. Culture can, then, be dissociated from the idea of a homogeneous, fi xed and transparent body of knowledge.
Keywords: Culture; Foreign language teacher education; Foreign language teaching; Teletandem